Knowledge, Attitude and Practice of Community Pharmacists Toward Non-pharmaceutical Products in Saudi Arabia - Dalia Almaghaslah (Frontiers in Public Health, 2022)
IntroductionCommunity pharmacy is a rapidly changing sector in Saudi Arabia. Customers visit local community pharmacies for a variety of reasons including disease-related advice, buying OTC medication, cosmetic products and re-filling a prescription for a chronic illness. The current study was conducted to fill the gap in the literature regarding community pharmacists' knowledge, attitude and practice toward non-pharmaceutical products.MethodsThe study used a cross-sectional design. A total of 211 community pharmacists working in the Asir region, Saudi Arabia were included. The questionnaire was adopted from a previous study with the same purpose.ResultsProducts sold in community pharmacies were mainly pharmaceutical products (69.7%) compared to 30.3% non-pharmaceutical products. The most commonly sold non-pharmaceutical products were mother and baby products (26%) and skin care products (19%). Pharmacists showed good mean knowledge (3.96 out of 5), mean positive attitude (3.79 out of 5) and mean positive practice (3.32 out of 5).ConclusionCommunity pharmacists showed considerable knowledge pertaining to non-pharmaceutical products. Respondents demonstrated positive attitudes toward the non-pharmaceutical products and were interested in expanding their knowledge on the topic through continuing education. Additionally, they showed social accountability by assuming responsibility for providing patient counseling on non-pharmaceutical products.